2020
DOI: 10.6007/ijarbss/v10-i5/7219
|View full text |Cite
|
Sign up to set email alerts
|

Teaching at the Times of COVID-19: Inferences and Implications for Higher Education Pedagogy

Abstract: In our study, conducted during the first two months of the COVID-19 pandemic in Greece, we trace the instant effects of the crisis conditions on the university education. We examine the case of a Department of Education at the University of Patras, in order to investigate the students' assumptions and emotions on the sudden shift to online teaching, in the frame of two academic courses during crisis. Having in mind that University of Patras was one of the first institutions in Greece that responded to the lock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
106
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 5 publications
7
106
1
9
Order By: Relevance
“…Contrary to the results of a study by Karalis and Raikou (2020) in Greece which reported that participation in online classes was high, there were attendance and participation problems in the present study and a high rate of students who missed their online classes.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to the results of a study by Karalis and Raikou (2020) in Greece which reported that participation in online classes was high, there were attendance and participation problems in the present study and a high rate of students who missed their online classes.…”
Section: Discussioncontrasting
confidence: 99%
“…Findings of the present study are consistent with findings of other studies in the literature. As in prior studies by Ghounane (2020), Koçoglu and Tekdal (2020), Karalis and Raikou (2020), Adnan and Anwar (2020), Baber (2020), Al-Nofaie (2020), students in the present study preferred face-to-face instruction and interaction rather than virtual learning via Blackboard, Microsoft Teams or Zoom.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…For students who already have an increased psychological distress [5.6], the quarantine period and distant education also increased their anxiety and stress levels. Initial studies showed that, especially in the first weeks of quarantine, students had very high stress levels [7]. Students also developed reactions linked to stress due to unknown serious infectious diseases [8].…”
Section: Introductionmentioning
confidence: 99%